Automatic Fiber Thickness Measurement in Scanning Electron Microscopy Images Validated Using Synthetic Data. Issue 3 (3rd February 2016) - Easwaran, Prakash; Lehmann, Martin J.; Wirjadi, Oliver; Prill, Torben; Didas, Stephan; Redenbach, Claudia
Abstract: Among the various properties of fibrous filter media, fiber thickness is one of the important characteristics which should be considered in design and quality assurance of filter media. Automatic analysis of images from scanning electron microscopy (SEM) is a suitable tool in that context. Yet, the accuracy of such image analysis tools cannot be judged based on images of real filter media since their true fiber thickness can never be known accurately. A solution is to employ synthetically generated models for evaluation. To this end, a 3D fiber model is extended to incorporate fiber bundles, which are common in fibrous filter media. The resulting novel stochastic 3D fiber model can generate geometries with good visual resemblance of real filter media. By combining this model with simulation of the SEM imaging process, quantitative evaluation of the fiber thickness measurements becomes feasible. Abstract : An innovative validation technique using synthetic data is introduced to evaluate existing automatic fiber thickness measurements more precisely. For this purpose, a 3D fiber system model for densely packed non‐overlapping fiber systems with fiber bundles is proposed, aiming at photorealistic simulation of scanning electron microscopy images of certain fibrous filter media's microstructures.